2021
DOI: 10.1038/s41398-020-01135-3
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress marker aberrations in children with autism spectrum disorder: a systematic review and meta-analysis of 87 studies (N = 9109)

Abstract: There is increasing awareness that oxidative stress may be implicated in the pathophysiology of autism spectrum disorder (ASD). Here we aimed to investigate blood oxidative stress marker profile in ASD children by a meta-analysis. Two independent investigators systematically searched Web of Science, PubMed, and Cochrane Library and extracted data from 87 studies with 4928 ASD children and 4181 healthy control (HC) children. The meta-analysis showed that blood concentrations of oxidative glutathione (GSSG), mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
72
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 45 publications
8
72
0
14
Order By: Relevance
“…The lower SAM/SAH ratio is indicative of impaired methylation capacity and a lower GSH with elevated GSSG represents impaired redox capacity [8]. These initial findings have been confirmed in several other prospective, controlled studies in blood [9][10][11][12] and brain samples [13][14][15], and a meta-analysis has confirmed the consistency of these findings across multiple studies and multiple laboratories [5]. A meta-analysis of 22 studies confirmed a consistent finding of impaired DNA methylation in ASD [16] and impaired DNA methylation has been associated with mitochondrial dysfunction in ASD [17].…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…The lower SAM/SAH ratio is indicative of impaired methylation capacity and a lower GSH with elevated GSSG represents impaired redox capacity [8]. These initial findings have been confirmed in several other prospective, controlled studies in blood [9][10][11][12] and brain samples [13][14][15], and a meta-analysis has confirmed the consistency of these findings across multiple studies and multiple laboratories [5]. A meta-analysis of 22 studies confirmed a consistent finding of impaired DNA methylation in ASD [16] and impaired DNA methylation has been associated with mitochondrial dysfunction in ASD [17].…”
Section: Introductionmentioning
confidence: 60%
“…Lastly, some individuals with ASD have lower intake and blood levels of B12 compared to controls. For example, a meta-analysis of 29 studies reported children with ASD had a significantly lower dietary intake of B12 compared to controls [ 64 ], while another meta-analysis of 16 studies found plasma B12 concentrations significantly lower in ASD compared to controls, although evidence of potential publication bias was found [ 5 ]. These finding may be due to feeding difficulties, which are common in individuals with ASD [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the evidence for markers of oxidative stress associated with glutathione metabolism, lipid peroxidation, protein oxidation, DNA oxidation and antioxidant enzyme activity has been comprehensively reviewed in recent years [45,[98][99][100][101][102][103]. In the context of neurodevelopment, this has significant implications for the redox regulation of neurogenesis.…”
Section: Discussionmentioning
confidence: 99%